2021
DOI: 10.3390/ma14237187
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Copper (II) from Aqueous Solutions with Alginate/Clay Hybrid Materials

Abstract: Massive amounts of industrial and agricultural water around the world are polluted by various types of contaminants that harm the environment and affect human health. Alginic acid is a very versatile green polymer used for heavy metal adsorption due to its availability, biocompatibility, low cost, and non-toxic characteristics. The aim of this paper was to prepare new low-cost hybrid composite beads using sodium alginate with treated montmorillonite and kaolin for the adsorption of copper (Cu) cations. Modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…At low conc of Cu(II) ions, decreased removal with increasing initial conc was ascribed to the elevated driving force in terms of biosorbents binding sites accessible and available, whereas the increased struggle for limited sorptions sites at elevated conc led to reduced removal of Cu(II) ions and thus more Cu(II) ions are left unabsorbed in the solutions due to the rapid saturations of sorptions sites. These assertions reported in this study are also supported by the study of Gupta et al[22], Larous and Meniai[64], Eldeeb et al[67], Yu et al[71], and Râpă et al[72].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…At low conc of Cu(II) ions, decreased removal with increasing initial conc was ascribed to the elevated driving force in terms of biosorbents binding sites accessible and available, whereas the increased struggle for limited sorptions sites at elevated conc led to reduced removal of Cu(II) ions and thus more Cu(II) ions are left unabsorbed in the solutions due to the rapid saturations of sorptions sites. These assertions reported in this study are also supported by the study of Gupta et al[22], Larous and Meniai[64], Eldeeb et al[67], Yu et al[71], and Râpă et al[72].…”
supporting
confidence: 91%
“…These results show that the biosorption of Cu(II) to the biochars was a rate-limiting step that has valence force between the biochars and the sorbate, with electron exchange or sharing [28]. Râpă et al [72] equally found in their biosorption of Cu(II) ions to alginate/clay hybrid composite beads study that the PSO model best described the biosorption process [72]. While in the studies of Bai et al [80], Hu et al [82], and Khan et al [81] where Humulus scandens-derived biochar, biochar derived from Chaenomeles sinensis seed, and muskmelon peel biochar were utilized for the biosorption of Cu(II) ions, it was noticed that the biosorption processes were best close-fitting to the experimental data using the PSO model [86][87][88][89][90][91][92][93].…”
Section: Biosorption Kineticsmentioning
confidence: 83%
“…Adsorption is widely used for the removal of contaminants from aqueous solutions, being cost-effective and environmentally friendly [92][93][94]. The possible factors affecting the removal efficiency of MPs/NPs by adsorption include: pH, temperature, adsorbent types, dissolved organic matter (DOM), and ions [72].…”
Section: Adsorptionmentioning
confidence: 99%
“…Continuous copper accumulation in the environment results from human activities, including industrialization, waste from copper mines, and poor waste management of copper-containing materials such as from electric wires, analytical reagents, and electroplating [6]. The United States Environment Protection Agency has recommended maximum drinking water copper concentration limits of 1.3 mg L −1 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This, however, depends on the adsorbents used. Activated carbon, biochar, and clay are some of the common adsorbents used for water treatment [7,12]. Both activated carbon and biochar are characterized by large surface areas and surface functional groups that aid the removal of contaminants.…”
Section: Introductionmentioning
confidence: 99%